RBD-specific polyclonal F(ab´)2 fragments of equine antibodies in patients with moderate to severe COVID-19 disease: A randomized, multicenter, double-blind, placebo-controlled, adaptive phase 2/3 clinical trial. (April 2021) - Lopardo, Gustavo; Belloso, Waldo H.; Nannini, Esteban; Colonna, Mariana; Sanguineti, Santiago; Zylberman, Vanesa; Muñoz, Luciana; Dobarro, Martín; Lebersztein, Gabriel; Farina, Javier; Vidiella, Gabriela; Bertetti, Anselmo; et al.
Abstract: Background: passive immunotherapy is a therapeutic alternative for patients with COVID-19. Equine polyclonal antibodies (EpAbs) could represent a source of scalable neutralizing antibodies against SARS-CoV-2. Methods: we conducted a double-blind, randomized, placebo-controlled trial to assess efficacy and safety of EpAbs (INM005) in hospitalized adult patients with moderate and severe COVID-19 pneumonia in 19 hospitals of Argentina. Primary endpoint was improvement in at least two categories in WHO ordinal clinical scale at day 28 or hospital discharge (ClinicalTrials.gov number NCT04494984). Findings: between August 1st and October 26th, 2020, a total of 245 patients were enrolled. Enrolled patients were assigned to receive two blinded doses of INM005 ( n = 118) or placebo ( n = 123). Median age was 54 years old, 651% were male and 61% had moderate disease at baseline. Median time from symptoms onset to study treatment was 6 days (interquartile range 5 to 8). No statistically significant difference was noted between study groups on primary endpoint (risk difference [95% IC]: 528% [-395; 1450]; p = 015). Rate of improvement in at least two categories was statistically significantly higher for INM005 at days 14 and 21 of follow-up. Time to improvement in two ordinal categories or hospital discharge was 142 (± 07) days in the INM005 group and 163 (± 07) days in the placebo group, hazard ratio 131 (95% CI 10 to 174). Subgroup analyses showed a beneficial effect of INM005 over severe patients and in those with negative baseline antibodies. Overall mortality was 69% the INM005 group and 114% in the placebo group (risk difference [95% IC]: 057 [024 to 137]). Adverse events of special interest were mild or moderate; no anaphylaxis was reported. Interpretation: Albeit not having reached the primary endpoint, we found clinical improvement of hospitalized patients with SARS-CoV-2 pneumonia, particularly those with severe disease.